Leader-Follower Congruence in Proactive Personality and Work Outcomes: The Mediating Role of Leader-Member Exchange - Zhang, Zhen; Wang, Mo; Shi, Junqi (Academy of Management Journal, 2012)
Drawing upon prior research on proactive personality and person-environment fit, we examine the congruence effect of leader and follower proactive personality on leader-member exchange (LMX) quality, which in turn influences follower job satisfaction, affective commitment, and job performance. Results of cross-level polynomial regressions on 165 dyads supported the congruence effect hypothesis. Further, asymmetrical incongruence effects were found wherein followers had lower-quality LMX and poorer work outcomes when their proactive personality was lower than their leaders' as compared with when their proactive personality was higher. These findings highlight the pivotal role played by leaders in promoting employee proactivity at work.